СООТНОШЕНИЕ ПОЛОВ У ПАРАЗИТИЧЕСКИХ НЕМАТОД И МЕХАНИЗМЫ ЕГО ФОРМИРОВАНИЯ (Experimental biology, 2009)
On the ground of the analysis of field and experimental data on sex proportion of parasitic nematodes the proposition about the forming of ration between males and females in parasites’ populations. It was proposed that the forming of sex proportion between adult nematodes was realized on the several stages and was the compoundmechanism including the death of numerous immature and old males and the influence of external factors and measure of larvae to their transformation to males or females.
Keywords: parasitic